Pengenalan Gerakan Sikap Dasar Pencak Silat Bakti Negara berbasis Aplikasi Mobile menggunakan Neural Network - Suantara, I Putu Julian Taruna; Fredlina, Ketut Queena; Sudiatmika, Ida Bagus Kresna (Jurnal Teknologi Terpadu, 2022)
Research on introducing basic stance or poses recognition specializing in sports is scarce. Researchers have not yet found journals or articles that discuss the introduction of the fundamental view of Pencak Silat as in this research. The research results can be used by athletes, teaching staff or organizations, and even the government who want to take advantage of the results of this research in the form of an application to introduce the fundamental stance of Pencak Silat. To realize this application, researchers use Neural Network or artificial intelligence where the model of recognition is trained on the Teachable Machine, which produces recognition accuracy above 90%, then integrated with mobile application programs based on Android that have been built using Flutter. After being integrated whit the mobile application, This application recognition still produces accuracy above 90%, so it can be concluded this application can work very well.